Peningkatan Kesadaran Budaya K3 Siswa Teknik Alat Berat SMK Duta Bangsa - Kisanjani, Alex; Astuti, Dwi; Oktaviana, Virza; Wagimin; Andivas, Marulan (Jurnal Pengabdian UntukMu NegeRI, 2026)
This community service activity, consisting of socialization and training on Occupational Health and Safety (OHS), was conducted at SMK Duta Bangsa Balikpapan to address the low awareness of OHS implementation among students, particularly in the Heavy Equipment Engineering major. The primary issues identified were the minimal use of Personal Protective Equipment (PPE) and a lack of compliance with safe working procedures. The methods employed included initial observation, socialization of basic OHS concepts, PPE usage simulation, equipment inspection, and emergency response roleplay. Evaluation was carried out through random question-and-answer sessions to measure cognitive aspects, as well as direct observation of changes in student behavior and skills. The results demonstrated a significant increase in students' knowledge, skills, and compliance regarding OHS application. Furthermore, a safety-first work culture was established in the practical workshop, reinforced by the active supervisory role of the teachers. This program not only improves OHS literacy but also delivers a long-term impact by instilling professional and safe work habits from an early stage, aligning with the actual needs of the industrial sector.